Saltbush-associated Asphondylia species (Diptera: Cecidomyiidae) in the Mediterranean Basin and their chalcidoid parasitoids (Hymenoptera: Chalcidoidea) - Dorchin, Netta; Mifsud, David; Askew, Richard (Zootaxa, 2014)
Numerous species of gall midges (Diptera: Cecidomyiidae) have been recorded from saltbush (Chenopodiaceae: Atriplex) around the world but only 11 of them belong to the large cecidomyiid genus Asphondylia. Of these, two species were described in the late 19th century from complex bud galls on Atriplex halimus in the Mediterranean Basin. In the present study Asphondylia punica is redescribed, A. conglomerata is synonymized with it, and Asphondylia scopuli is described from Atriplex lanfrancoi, an endemic plant to the Maltese Islands. Descriptions are accompanied by information about the galls and life history of the gall midges, and a review of the parasitic Hymenoptera associated with A. scopuli is provided. Four species of parasitoids were found and attributed to the families Eurytomidae, Pteromalidae, Eupelmidae and Eulophidae, of which the pteromalid Mesopolobus melitensis is described as new.